2009
DOI: 10.1063/1.3271392
|View full text |Cite
|
Sign up to set email alerts
|

Exact Kohn–Sham potential of strongly correlated finite systems

Abstract: The dissociation of molecules, even the most simple hydrogen molecule, cannot be described accurately within density functional theory because none of the currently available functionals accounts for strong on-site correlation. This problem has led to a discussion of properties that the local Kohn-Sham potential has to satisfy in order to correctly describe strongly correlated systems. We derive an analytic expression for this potential at the dissociation limit and show that the numerical calculations for a o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(179 citation statements)
references
References 28 publications
4
175
0
Order By: Relevance
“…The diagonal contributions to the Hessian are readily evaluated to be (35) and the off-diagonal elements become (i = j)…”
Section: B Calculation Of the Zero-point Energies (Zpe) In 1dmentioning
confidence: 99%
“…The diagonal contributions to the Hessian are readily evaluated to be (35) and the off-diagonal elements become (i = j)…”
Section: B Calculation Of the Zero-point Energies (Zpe) In 1dmentioning
confidence: 99%
“…Steps in the xc potential (a jump in the level of the xc potential over a relatively short distance) have been shown to be crucial for an accurate description of the electron density for a variety of ground-state and timedependent systems [5][6][7][8][9][10][11][12][13][14][15] , such as tunneling electrons and charge transfer/excitations. Atomic structure calculations by van Leeuwen et al 6 demonstrated that steps arise at the boundaries between atomic shells.…”
Section: Introductionmentioning
confidence: 99%
“…This model has two nice features: first the bonding and antibonding eigenstates are exactly known and they can be calculated by means of a superpotential, as it is done in supersymmetric quantum mechanics 43 ; second, in the limit of large inter-well distances, it reduces to a superposition of two Eckart wells 44 allowing to recover a model often used in molecular physics 45 .…”
Section: Numerical Solution For a Simple Two-atom Moleculementioning
confidence: 99%